Economics for managers [12th ed.] - McGuigan, James R.; Moyer, R. Charles; Harris, Frederick H. deB. (Andover Cengage Learning, 2011)
Packed with managerially oriented applications, ECONOMICS FOR MANAGERS, 12e, illustrates how managers apply theories and techniques to solve real-world problems while teaching future business leaders how to think analytically and make better decisions. Extremely user friendly, the text caters to a variety of learning styles as it presents key analytical concepts in several ways, including tabular analysis, graphical analysis and algebraic analysis. Students learn in a format with which they are comfortable, making difficult material more accessible and easier to understand. The new 12th edition is concise, current and cutting edge with an exciting and extremely relevant new focus
Keywords: Management; Economics